2017
DOI: 10.21701/bolgeomin.128.2.010
|View full text |Cite
|
Sign up to set email alerts
|

Reclamation of a mine tailings pond by addition of marble waste and pig slurry for the development of aided phytostabilization

Abstract: Zornoza, R. et al., 2017. Rehabilitación de una presa de residuos mineros mediante la aplicación de lodo de mármol y purín de cerdo para el desarrollo de una fitoestabilización asistida. Boletín Geológico y Minero, 128 (2) RESUMENLas acumulaciones de residuos mineros abandonados presentan riesgos ambientales y de salud pública por la potencial transferencia de metales pesados tóxicos a través de la erosión hídrica y eólica o lixiviación. Para reducir estos riesgos, se ha desarrollado una estrategia de rehabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 27 publications
0
4
0
3
Order By: Relevance
“…Similar results are observed in a study carried out in a limestone quarry in a semi-arid climate [53] in which organic amendments (sewage sludge and compost from domestic organic waste) were applied, where the soils showed higher N, P and K content than the soil without treatments. Another study [54] also showed that the application of amendments (marble waste and pig slurry) significantly increased soil N in an old mining waste dam recovery in a semi-arid climate. The application of pig manure increased soil N [59].…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Similar results are observed in a study carried out in a limestone quarry in a semi-arid climate [53] in which organic amendments (sewage sludge and compost from domestic organic waste) were applied, where the soils showed higher N, P and K content than the soil without treatments. Another study [54] also showed that the application of amendments (marble waste and pig slurry) significantly increased soil N in an old mining waste dam recovery in a semi-arid climate. The application of pig manure increased soil N [59].…”
Section: Discussionmentioning
confidence: 91%
“…The values similar to those obtained in this study were found in a study carried out in 2016 [53], in which several combinations of organic amendments (sewage sludge and compost from domestic organic waste) and mulches (gravel and woodchip) were applied in a quarry in a semi-arid climate. In another study carried out in 2017 [54], the pH was increased to values close to neutrality due to the presence of carbonate in the wastes; marble waste and pig slurry were used to rehabilitate a mining waste dam. With the application of other waste, for instance, from the olive oil industry, an increase in the soil pH was also found [55,56] even in calcareous soils.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Las especies vegetales, así como las enmiendas del suelo, se utilizan para la inmovilización de metales pesados a través de la absorción y acumulación por sus raíces o precipitación dentro de la rizosfera (Bolan et al, 2011). Estas especies vegetales deben ser capaces de desarrollarse en condiciones adversas, como suelos contaminados, y tener una alta capacidad de biomasa para maximizar la eliminación de metales pesados del suelo (Zornoza et al, 2017). Debido a que la revegetación natural en estos emplazamientos mineros puede ser lenta o bien inexistente debido a la pobre calidad del suelo, esta técnica puede resultar ser una opción efectiva para la rehabilitación de este tipo de emplazamientos.…”
Section: Remediación De Suelos Contaminados Por Metales Pesadosunclassified